(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: Sleep is one of the important and familiar parts of everyone’s life. It is one of the three pillars along with nutrition and exercise. Objective: The purpose of the present study is to find the association if exists, between self-reported sleep duration with Body mass index. Methodology: This is an exploratory study done in New Delhi, India among 100 adults aged 20-40 years using opportunity sampling method. Data on socio-demographic profile, self-reported sleep duration, body mass index were gathered from 100 subjects. Results: A significant negative correlation (p=.002) was observed between body mass index and self reported sleep duration. Conclusion: The current study establishes an association between the less duration of sleep and body mass index, which predisposes an individual for risk of developing Non-communicable diseases.